Sintesis Hidroksiapatit Dari Precipitated Calcium Carbonate (PCC) Cangkang Telur Itik Melalui Proses Pengendapan Dengan Variasi Rasio Ca/P Dan Kecepatan Pengadukan - Toni Arissaputra; Yelmida Yelmida; Fajril Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Hydroxyapatite (HAp) is the most stable form of calcium phosphate and is widely applied in the medical field because it’s properties is similar to the components in certain organs of the human body such as bones and teeth. The aims of this study were to synthesis hydroxyapatite from duck egg shell by precipitation method, studied the effect of Ca/P molar ratio and stirring speed on the hydroxyapatite product and compare the result for such variable. Synthesis HAp was done by three steps. First step was calcination duck eggshell to CaO. Second step, made PCC (Precipitated Calcium Carbonate). Third step, synthesis HAp used precipitation method. Variables used were molar ratio Ca/P 1.67;1.77;1.87 and stirring speed 200, 250, 300 rpm. HAp product was analized by FTIR, XRD, SEM-EDX and BET. The best HAp product was produced at a Ca / P molar ratio and stirring rate at 1.67 and 300 rpm respectively. HAp crystals are hexagonal with a diameter of 23.086 nm. HAp has high purity without contaminated with any other elements and is in the form of agglomerates. The molar ratio of Ca / P results was obtained at 1.55 and the surface area of the HAp was 55.929 m2/g.Keywords : Calcium Phospate, Duck Eggshell, Hydroxyapatite, Precipitation, Synthesis.